EFEKTIVITAS MODEL PROBLEM BASED LEARNING BERBANTUAN MIND MAP TERHADAP KEMAMPUAN PEMECAHAN MASALAH FISIKA - Agus Hariyanto (Jurnal Pendidikan dan Kebudayaan, 2015)
The purpose of this study is to determine the effectiveness of problem based learning models, aided with mind map, on student’s ability to solve problems creatively based on prior knowledge. Results of the study showed that: 1) students who studied with the PBL mind map-aided model had higher creative problem-solving ability than students who studied with only PBL, 2) in terms of higher prior knowledge, students who studied with the PBL mind map-aided model had higher creative problem-solving ability than students who studied with only PBL, 3) in terms of lower prior knowledge, students who studied with the PBL mind map-aided model had higher creative problem-solving ability than students who studied with only PBL, 4) The learning model used interacts with students’ prior knowledge and students’ creative problem-solving ability, 5) the creative problem-solving ability of students who used the PBL mind map-aided model was more effective than the creative problem solving ability of students with greater prior knowledge who used PBL models; 6) The creative problem-solving ability of students who used the PBL mind mapaided model was more effective than students with low prior knowledge who used the PBL learning model; 7) the creative problem-solving ability of students who used the PBL mind map-aided model was more effective than students who used the PBL learning model. It can be concluded that the PBL mind map-aided model is more effective than the PBL learning model in developing creative problem-solving abilities in 10th grade students, regardless of their prior knowledge levels.ABSTRAK Tujuan penelitian ini adalah untuk menguji efektivitas model problem based learning berbantuan mind map terhadap kemampuan pemecahan masalah fisika secara kreatif ditinjau dari kemampuan awal siswa kelas X. Penelitian ini menggunakan metode survei. Hasil penelitian menunjukkan bahwa: 1) Kemampuan pemecahan masalah fisika secara kreatif yang belajar dengan model PBL berbantuan Mind Map lebih tinggi dibandingkan pembelajaran PBL; 2) Kemampuan pemecahan masalah fisika secara kreatif siswa yang belajar dengan pembelajaran model PBL berbantuan mind map lebih tinggi dibandingkan pembelajaran PBL untuk siswa yang memiliki kemampuan awal tinggi; 3) Kemampuan pemecahan masalah fisika secara kreatif siswa yang belajar dengan pembelajaran model PBL berbantuan Mind Map lebih tinggi dibandingkan pembelajaran PBL untuk siswa yang memiliki kemampuan awal rendah;  4) Terdapat interaksi antara model pembelajaran dengan kemampuan awal terhadap kemampuan pemecahan masalah fisika secara kreatif; 5) Kemampuan pemecahan masalah fisika secara kreatif pebelajar dengan model PBL berbantuan mind map lebih efektif dibandingkan dengan model pembelajaran PBL untuk siswa yang memiliki kemampuan awal tinggi; 6) Kemampuan pemecahan masalah fisika secara kreatif pebelajar dengan model PBL berbantuan mind map lebih efektif dibandingkan dengan model pembelajaran PBL untuk siswa yang memiliki kemampuan awal rendah; 7) Kemampuan pemecahan masalah fisika secara kreatif pebelajar dengan model PBL berbantuan mind map lebih efektif dibandingkan dengan model pembelajaran PBL. Penelitian ini menyimpulkan bahwa model PBL berbantuan mind map lebih efektif dibandingkan dengan model pembelajaran PBL terhadap kemampuan pemecahan masalah fisika secara kreatif ditinjau dari kemampuan awal siswa kelas x.